Data mining techniques on astronomical spectra data – I. Clustering analysis. Issue 4 (20th September 2022) - Yang, Haifeng; Shi, Chenhui; Cai, Jianghui; Zhou, Lichan; Yang, Yuqing; Zhao, Xujun; He, Yanting; Hao, Jing
ABSTRACT: Clustering is an effective tool for astronomical spectral analysis, to mine clustering patterns among data. With the implementation of large sky surveys, many clustering methods have been applied to tackle spectroscopic and photometric data effectively and automatically. Meanwhile, the performance of clustering methods under different data characteristics varies greatly. With the aim of summarizing astronomical spectral clustering algorithms and laying the foundation for further research, this work gives a review of clustering methods applied to astronomical spectra data in three parts. First, many clustering methods for astronomical spectra are investigated and analysed theoretically, looking at algorithmic ideas, applications, and features. Secondly, experiments are carried out on unified datasets constructed using three criteria (spectra data type, spectra quality, and data volume) to compare the performance of typical algorithms; spectra data are selected from the Large Sky Area Multi-Object Fibre Spectroscopic Telescope (LAMOST) survey and Sloan Digital Sky Survey (SDSS). Finally, source codes of the comparison clustering algorithms and manuals for usage and improvement are provided on GitHub.